Genetic diversity of the species Leporinus elongatus (Teleostei: Characiformes) in the Canoas Complex - Paranapanema River - Ramos,Juliano Vilas Boas (2012)
Dams constructed along waterways interrupt the dispersion and migration of aquatic organisms, affecting mainly the abundance of migratory fish species. Translocation mechanisms have been constructed at dams aiming to minimize their impact on fish species migration behavior. There is little information available about the effect of the construction of dams on the genetic structure of the Neotropical migratory fish fauna. Therefore, RAPD molecular markers and microsatellites were utilized to evaluate the diversity and genetic structure of the migratory species Leporinus elongatus (piapara) in the Canoas Complex - Paranapanema River - Brazil. Ten groups were sampled in the fish ladders of the hydroelectric dam Canoas I and Canoas II during the reproductive period in three consecutive years. Both markers showed a high level of genetic diversity within these groups. The microsatellite markers demonstrated a loss of heterozygosity and a considerable level of inbreeding in the species. The genetic differentiation found among the groups with both markers utilized is within a range from low to moderate. The data obtained with the parameter of genetic diversity among the groups led to the conclusion that the groups of L. elongatus of the Canoas Complex are structured as a single population composed of sub-populations with low genetic diversity among them. The data on genetic diversity and population structure of L. elongatus are of great importance for the development of the species management and conservation programs in the Canoas Complex, which can also be utilized in aquaculture programs.